Transduction by adeno-associated virus vectors in the rabbit airway: efficiency, persistence, and readministration. - Halbert, C L (1997)
The ability of recombinant adeno-associated virus (AAV) vectors to integrate into the host genome and to transduce nondividing cells makes them attractive as vehicles for gene delivery. In this study, we assessed the ability of several AAV vectors to transduce airway cells in rabbits by measuring marker gene expression. AAV vectors that transferred either a beta-galactosidase (beta-gal) or a human placental alkaline phosphatase (AP) gene were delivered to one lobe of the rabbit lung by use of a balloon catheter placed under fluoroscopic guidance. We observed vector-encoded beta-gal or AP staining almost exclusively in the epithelial and smooth muscle cells in the bronchus at the region of balloon placement. The overall efficiency of transduction in the balloon-treated bronchial epithelium was low but reached 20% in some areas. The majority of the staining was in ciliated cells but was also observed in basal cells and airway smooth muscle cells. We observed an 80-fold decrease in marker-positive epithelial cells during the 60-day period after vector infusion, whereas the number of marker-positive smooth muscle cells stayed constant. Although treatment with the topoisomerase inhibitor etoposide dramatically enhanced AAV transduction in primary airway epithelial cells in culture, treatment of rabbits did not improve transduction rates in the airway. Vector readministration failed to produce additional transduction events, which correlated with the appearance of neutralizing antibodies. These results indicate that both readministration and immune modulation will be required in the use of AAV vectors for gene therapy to the airway epithelium.